Meta-analysis of financial performance and cross-listing of Indian and Chinese firms. (2016) - Lakshmi, P.; Visalakshmi, S.
This paper examines the transmission of information and the influence of arbitrage trading between index returns of developed US markets and returns of cross-listed stocks [American Depository Receipts (ADRs) and dollar returns of their respective underlying stocks] and their financial performance in two emerging markets viz., India and China by applying VAR-SURE model, variance decomposition and impulse response function. The results of VAR-SURE model indicate that on the same day, both Indian and Chinese ADRs are close substitutes of their domestic counterparts and not much is available to international investors through arbitrage. The VDC results indicate that the Indian stocks, ADRs are influenced by their own lags but contradictorily the Chinese stocks are influenced by their ADR return movements on the same day. The impulse responses also render support to the VAR, VDC findings in all the variables in both the Indian and Chinese markets. Among the two emerging economies under study, though the ADRs of both the countries are influenced by the US markets, Chinese domestic stock prices are more sensitive to changes in the US markets.